2013
DOI: 10.1371/journal.pone.0063613
|View full text |Cite|
|
Sign up to set email alerts
|

Notch Ligand Delta-Like 4-Pretreated Dendritic Cells Alleviate Allergic Airway Responses by Enhancing IL-10 Production

Abstract: The Notch pathway plays a role in the processes of cell proliferation, differentiation, and apoptosis, which affect the development and function of various organs. Dendritic cells (DCs), as professional antigen-presenting cells (APCs), induce T cell activation and promote T cell differentiation by antigen stimulation. Research has shown that Notch ligand delta-like 4 (Dll4) in APCs is associated with stimulation of a Th1-type response. However, the regulatory roles of Dll4 in the activation and function of DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…At 24 h after the final aerosol OVA exposure, in vivo lung function was measured by detecting changes in airway resistance in response to increasing doses of aerosolized methacholine (MCh, Sigma-Aldrich) in anesthetized mice as described previously [ 14 ]. MCh aerosol was generated with a nebulizer and administrated directly through the ventilator for 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…At 24 h after the final aerosol OVA exposure, in vivo lung function was measured by detecting changes in airway resistance in response to increasing doses of aerosolized methacholine (MCh, Sigma-Aldrich) in anesthetized mice as described previously [ 14 ]. MCh aerosol was generated with a nebulizer and administrated directly through the ventilator for 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Notch ligand expression on CD11c+ APCs has been implicated in modulating T-cell activation and cytokine production during a variety of disease states and immunological maladies 31 35 . To determine whether levels of Notch ligands were altered on APCs following BMT and viral infection, total CD11c+ cells were isolated by magnetic bead separation from either control or BMT mouse groups and infected ex-vivo at a multiplicity of infection of 1.0 for 24 h with γHV-68.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies noted the interaction between them: PD-1 could enhance IL-10 production [ 26 ] and IL-10 also induced PD-1 expression in monocytes and CD4 + T cells [ 27 ]. Additionally, previous research showed that DC matured by Jagged1 (Jgd1-conditioned DC) produced the high level of IL-10 through TLR (via LPS) signaling [ 28 ]. However, whether the Notch signaling pathway in regulation of PD-1 expression is through the IL-10 during sepsis-induced immunosuppression is unclear.…”
Section: Discussionmentioning
confidence: 99%